PERAN PEMERINTAH DESA DALAM PENINGKATAKAN KESEJAHTERAAN MASYARAKAT DI DESA ANDINETE KECAMATAN KOLONO KABUPATEN KONAWE SELATAN - Asmin; Patta Hindi; Yunitawati Lampasa; Riston G Ahmad (Journal Publicuho, 2025)
This study aims to describe and analyse the role of the village government in improving community welfare in Andinete Village, Kolono District, South Konawe Regency. A qualitative approach was employed using a descriptive method through in-depth interviews, direct observation, and document analysis. The findings indicate that the village government plays a crucial role in planning and implementing development programs, empowering the local economy, and providing basic social services. Programs such as direct cash assistance, skills training, and basic infrastructure development have had a positive impact on improving the community’s standard of living. However, challenges remain, including budget constraints, low community participation, and a lack of coordination between institutions. The study concludes that the active and collaborative role of the village government is vital for the success of sustainable efforts to enhance community welfare.